tinjauan konseptual tentang pengaruh influencer marketing terhadap keputusan pembelian konsumen Gen Z : literature riview - hidayah, nur laeli (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
Influencer marketing is an effective digital marketing strategy, particularly in reaching Generation Z, who are familiar with social media. This research is a literature review of six previous studies that discuss the role of influencer marketing and related factors in influencing Gen Z purchasing decisions. The literature analysis shows that influencer credibility, social media interactivity, electronic word of mouth (E-WoM), and digital marketing content contribute significantly to the formation of brand loyalty, brand love, and purchase intention, which ultimately influence purchasing decisions. The results of this review reinforce the concept that the success of influencer marketing depends heavily on message relevance, emotional connection with the audience, and the fit between the influencer's image and the brand.